Pancasila sebagai Dasar Negara dan Hukum Internasional Implementasi Nilai-nilai Kemanusiaan dalam Kebijakan Luar Negeri Indonesia - Ahmad Muhamad Mustain Nasoha; Ashfiya Nur Atqiya; Aurellia Zahra Putri Areje; Lailatul Allifah; Siti Norhalisa (LP3M INSTITUT KH YAZID KARIMULLAH, 2025)
Pancasila, as the foundational philosophy of Indonesia, plays a central role in shaping national policies, including foreign policy. This paper aims to explore the implementation of Pancasila values in Indonesia's foreign policy, focusing on how humanitarian principles are integrated into diplomatic practices and international law. The study employs a qualitative approach by analyzing recent literature, policy reports, and interviews with relevant experts. The findings reveal that Pancasila, particularly the principle of Just and Civilized Humanity, serves as a moral guide in foreign policy decision-making. However, the application of these values often faces challenges due to global political dynamics and competing national interests. The evaluation shows that while there are efforts to align foreign policy with Pancasila’s humanitarian principles, there remains a need to enhance consistency and effectiveness in their implementation. This research aims to provide insights into how Indonesia can improve the integration of Pancasila values in its foreign policy and contribute to a more just and humane international legal framework.